Carbapenem Consumption and Rate of carbapenemresistant gram-negative bacteria: results from the Sicilian Surveillance System - Barchitta, M.; Maugeri, A.; La Rosa, M. C.; La Mastra, C.; Murolo, G.; Basile, G.; Agodi, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. In the last decades, multidrug-resistant gram-negative bacteria have been increasing and they are involved in severe healthcare associated infections. In treating drug-resistant gram-negative bacterial infections, carbapenems are generally administered as a last choice. However, the rate of carbapenemresistant bacteria is constantly increasing the last years. The aim of the present study is to describe the relationship between the rate of carbapenem-resistant gram-negative bacteria and antibiotic consumption intensity. Study design. In 2017, the Sicilian Region implemented a regional surveillance system to describe and analyze consumption of antibiotics in hospital settings, as well as prevalence of antibiotic resistant microorganisms. Methods. Resistance data were retrospectively collected from routinary clinical antimicrobial susceptibility tests. Resistance rates (RRs) of carbapenems were calculated and Spearman’s correlation analysis was performed to investigate the relationship between annual antibiotic consumption and rate of carbapenem resistance. Results. In 2015, the overall prevalence of carbapenem-resistant Klebsiella pneumoniae isolates was 43.9 %, and was positively correlated with beta-lactam consumption (R=0.529, p<0.01), and with carbapenem consumption (R=0.364, p<0.05). In 2016, the overall prevalence of carbapenem-resistant Klebsiella pneumoniae isolates was 53.8 %, and was positively correlated with carbapenem antibiotic consumption (R=0.364, p<0.05). In 2017, the overall prevalence of carbapenem-resistant Klebsiella pneumoniae isolates was 58.7 %, and was significantly positively correlated with carbapenem antibiotic consumption (R=0.427, p<0.05). In 2015, the overall prevalence of carbapenem-resistant Escherichia coli isolates was 6.5 %, and was significantly positively correlated with antibiotic consumption for the ATC class J01 (i.e., antibacterial for systemic use) (R=0.402, p<0.05). Conclusion. The results of the present study highlight the need for comprehensive strategies targeting the appropriate use of antibiotics and infection control measures.